Pelatihan Penulisan Sitasi dan Daftar Pustaka secara Manual bagi Mahasiswa untuk Penulisan Karya Tulis Ilmiah - Dedi Aprianto; Sutarman; Lela Rahmawati; Alfian Sayuti; Rina Komala (Jurnal Ilmiah Pengabdian dan Inovasi, 2024)
Students are faced with the challenge of producing quality and credible scientific papers. One important aspect of scientific papers is mastering citation and reference writing. This skill is often a weakness for students, thus triggering the desire to conduct community service. This community service aims to improve students’ ability to master the practice of manual citation and reference writing. The method used for this a community service was a training employed through lecturing, demonstrating, making group-discussion, and practicing. Hopefully, the program can improve the quality of students' scientific papers. The training program is important for the scientific papers, which was implemented for students. The results describe that equipping students with manual skills in citation and improving the quality of academic writing is urgent. The success of the program was evident with high participant satisfaction and significant improvement in the mean scores of the students’ feedback; satisfaction with training materials (4.28), satisfaction with the instructors (4.22), satisfaction with training facility (4.09), satisfaction with participant engagement (3.94), and level of understanding and application (4.20). Overall, the mean score is 4.1. The evaluation results suggest significant improvement in the pre-test’s mean score (61.65) and the post-test’s mean score (89.46). The program is expected to imply that students have an increased ability to compose quality scientific writings with accurate citations and references accurately and academically.